Conflict between morphology and molecular data: a case of the genus Caryophyllaeus (Cestoda: Caryophyllidea), monozoic tapeworms of cyprinid fishes - Bazsalovicsová, Eva; Králová-Hromadová, Ivica; Brabec, Jan; Hanzelová, Vladimíra; Oros, Mikulás; Scholz, Tomás (Folia parasitologica, 2014)
Molecular analysis of an extensive specimen collection of morphologically distinct tapeworms of the genus Caryophyllaeus Gmelin, 1790 (Cestoda: Caryophyllidea), parasites of cyprinid fishes in the Palaearctic Region, brought evidence of host-related plasticity in critical morphological characters widely used for species circumscription and classification of these tapeworms. The results obtained here do not support the traditionally used morphological concept of species-defining characters of the order Caryophyllidea Carus, 1863, especially due to high morphological plasticity of the scolex and the anterior end of the body. Several morphotypes within both Caryophyllaeus laticeps (Pallas, 1781) and Caryophyllaeus brachycollis Janiszewska, 1953 generally corresponding to different hosts and geographical regions, were recognised likely suggesting host- and geography-related intraspecific morphological variability. Genetic data confirmed euryxenous host specificity of both species, most profoundly C. laticeps, but did not support the existence of cryptic species. In fact, some of the fish hosts may harbour both of the congeneric species including several of their respective morphotypes. The pattern of morphological and genetic divergence observed in both cestode species studied indicates a scenario of possible host range extensions and subsequent parasite diversification. If molecular sequence variability and host-related morphological polymorphism are confirmed in other groups of monozoic cestodes, it may complicate species identification and straightforward classification of these parasites.
Keywords: Cestoda; Fish Diseases; regulace genové exprese enzymů; cestodózy; zvířata; DNA, Helminth; Cestode Infections; Electron Transport Complex IV; nemoci ryb; DNA helmintů; Cyprinidae; fylogeneze; DNA, Ribosomal; ribozomální DNA; respirační komplex IV; Phylogeny; Gene Expression Regulation, Enzymologic; Animals